3-D reconstruction of rice leaf tissue for proper estimation of surface area of mesophyll cells and chloroplasts facing intercellular airspaces from 2-D section images. (25th October 2022) - Ouk, Rachana; Oi, Takao; Sugiura, Daisuke; Taniguchi, Mitsutaka
Abstract: Background and Aims: The surface area of mesophyll cells ( S mes ) and chloroplasts ( S c ) facing the intercellular airspace (IAS) are important parameters for estimating photosynthetic activity from leaf anatomy. Although S mes and S c are estimated based on the shape assumption of mesophyll cells (MCs), it is questionable if the assumption is correct for rice MCs with concave–convex surfaces. Therefore, in this study, we establish a reconstruction method for the 3-D representation of the IAS in rice leaf tissue to calculate the actual S mes and S c with 3-D images and to determine the correct shape assumption for the estimation of S mes and S c based on 2-D section images. Methods: We used serial section light microscopy to reconstruct 3-D representations of the IAS, MCs and chloroplasts in rice leaf tissue. Actual S mes and S c values obtained from the 3-D representation were compared with those estimated from the 2-D images to find the correct shape-specific assumption (oblate or prolate spheroid) in different orientations (longitudinal and transverse sections) using the same leaf sample. Key Results: The 3-D representation method revealed that volumes of the IAS and MCs accounted for 30 and 70 % of rice leaf tissue excluding epidermis, respectively, and the volume of chloroplasts accounted for 44 % of MCs. The shape-specific assumption on the sectioning orientation affected the estimation of S mes and S c using 2-D section images with discrepancies of 10–38 %. Conclusions: The 3-D representation of rice leaf tissue was successfully reconstructed using serial section light microscopy and suggested that estimation of S mes and S c of the rice leaf is more accurate using longitudinal sections with MCs assumed as oblate spheroids than using transverse sections with MCs as prolate spheroids.